2021
DOI: 10.33448/rsd-v10i11.19571
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-terpineol: evaluation and pharmacological screening as an antidepressant agent

Abstract: Objective: To evaluate the possible antidepressant effects of alpha-terpineol in rodents. Material and Methods: Depression levels were analyzed by comparing the total immobility time presented by the animals of the experimental groups in the test session, using the Forced Swimming Test and the Tail Suspension Test. The parameters of locomotion (central, peripheral and total) and motor coordination were evaluated in the Open Field Test and in the Rota Rod Test, respectively. In the second stage, the involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was the main component of Oreganum majorana (Abbasi-Maleki et al, 2020). Assunção et al (2021) studied the effectiveness of alpha-terpineol to reduce depression through behavioral tests, which were the forced swim test and tail suspension test. The study showed that alpha-terpineol at doses 50 mg/kg and 100 mg/kg given orally demonstrated a lower immobility time than control groups which indicated its potency as an antidepressant agent.…”
Section: Resultsmentioning
confidence: 99%
“…It was the main component of Oreganum majorana (Abbasi-Maleki et al, 2020). Assunção et al (2021) studied the effectiveness of alpha-terpineol to reduce depression through behavioral tests, which were the forced swim test and tail suspension test. The study showed that alpha-terpineol at doses 50 mg/kg and 100 mg/kg given orally demonstrated a lower immobility time than control groups which indicated its potency as an antidepressant agent.…”
Section: Resultsmentioning
confidence: 99%